Opinions and needs of patients considering function in psychiatric ward - Perzyńska-Starkiewicz, Aneta; Zakrocka, Izabela; Stelmach, Ewa (Current Problems of Psychiatry, 2011)
The aim of study was to recognize patient’s opinions and needs concerning function in Psychiatric Department of Medical University in Lublin.An anonymous self-made questionnaire consisting of 20 questions was used in our analysis. 52 patients (25 males and 27 females) from Psychiatric Department took part in this study. The average age was 35,85 and the average duration of stay in the ward was 4,76 weeks.From the conducted analysis such conclusions were drawn: most of the patients are satisfied with the function in the psychiatric ward. Function in psychiatric ward was evaluated very well by a 33% of patients, good – by a 63% of patients and Bad – by a 4% of them.The aim of study was achieved. We recognized patients opinions and needs of function in psychiatric department. We should also think about the fact that our patients suffer from specific disorder which can have influence on their opinions.